Hydraulic Characteristics of Flow Over Triangular Broad Crested Weirs - Raad Hoobi Irzooki; Mohammad Faiq Yass (Engineering and Technology Journal, 2015)
In the present work, the hydraulic characteristics of flow over triangular broad crested weirs with triangular front or back face have been experimentally studied. The main objective of this research is to obtain empirical equation to estimate the value of the discharge coefficient (Cd) for this kind of weir and determine the factors that affect on it. For this purpose 18 models were constructed with different dimensions made of plexiglass and were tested in a laboratory flume of 6m length, 30cm width and 40cm height. These models divided into two groups, each group consists of 9 models. In the first group 108 experiments were conducted by changing the upper face angle of the weir three times (90°, 120°, 150°), the angle of the triangular front or back face (α) is also changed three times (90°, 120°, 150°), for each model six different discharges were passed. In the second group 54 experiments were carried out on models with a straight face on the front and back (α=180°) with changing the upper face angle (θ) three times (90°, 120°, 150°) and changing the height of the edge of the weir (P) three times ( 20 , 18 , 16 cm), for each model six different discharges were passed. Dimensional analysis was performed to obtain the dimensionless parameters that the discharge coefficient (Cd) depends on it. Results showed that the change in the angle of the triangular front or back face (α) have little effect on the discharge over these weirs, while it was noted that the height of the edge of the weir (P) affects on the discharge coefficient, where (Cd) increased with increasing (P). Also, the upper face angle of the weir (θ) has an effect on the discharge coefficient, where the discharge coefficient increased with decreasing the value of angle (θ). A simple empirical equation was predicted, in terms of the application, for the calculation of the discharge coefficient (Cd) of weirs that used in this study, there was a good agreement between the results obtained from this equation with the experimental results.